The Role of Social Capital Facing Pandemic COVID-19 in Tourism Village to Support Sustainable Agriculture (Empirical Evidence from Two Tourism Villages in Indonesia) - Aidha Auliah; Gunawan Prayitno; Ismu Rini Dwi Ari; Rahmawati; Lusyana Eka Wardani; Christia Meidiana (Economies, 2022)
Pujon Kidul and Bangelan villages (Indonesia) are two tourist villages that have succeeded in developing agricultural potential associated with tourism activities. The characteristics of Pujon Kidul Village and Bangelan Village refer to the tourism activities in the villages. This study aims to find out how community social capital can influence collective action in dealing with the COVID-19 pandemic in Pujon Kidul Tourism Village and Bangelan Tourism Village. This study uses the structural equation model (SEM) method, which is applied to the SEM, PLS (Partial Least Square) and AMOS (Analysis of Moment Structures) software to get complete results. The results of the analysis, Bangelan Village and Pujon Kidul Village are models that can survive in a pandemic crisis situation. The results of the model show that social capital in dealing with a pandemic in Bangelan Village is most influenced by trust in the government, while in Pujon Kidul Village it is most influenced by trust among fellow communities. The existence of social capital plays a role in decision-making on collective actions to deal with pandemics in tourist villages. Thus, by knowing how the community is recovering during the COVID-19 pandemic, businesses can run smoothly and according to government policy.